Existing developments in adaptive smart grid protection: A review - Khalid, Hammad; Shobole, Abdulfetah; Shobole, Abdulfetah Abdela (Elsevier Ltd, 2021)
The future smart power grid where Distributed Generations (DGs) are highly integrated and self-healing is required is intended to provide reliable and quality power in economic and environmentally friendly manner. This vision of the future power grid calls for a different solution in power system protection. This demand arises from the dynamic condition of the future Smart Grid, which is why a large number of protection techniques and methods have been researched and implemented over the years. Especially, the research on adaptive power protection techniques is immensely growing, as it is very desirable for the power system to change its own protection settings in real-time according to the system operating states and conditions. This literature survey presents a number of power system protection techniques being implemented with Smart Grids, however, the focus has been given to Adaptive Protection techniques. In this review, the previous adaptive protection research works are discussed and organized systematically to help researchers more effectively perform literature reviews and find relevant research works. Furthermore, the important components and draw backs of the adaptive protection is discussed, emphasizing on the gap which the researchers could engage in to improve the adaptive protection techniques. © 2020 Elsevier B.V.
Keywords: Adaptive protection; Distributed generation; Micro-grid; Smart grid